2021
DOI: 10.1042/bsr20210443
|View full text |Cite
|
Sign up to set email alerts
|

Responses and coping methods of different testicular cell types to heat stress: overview and perspectives

Abstract: To facilitate temperature adjustments, the testicles are located outside the body cavity. In most mammals, the temperature of the testes is lower than the body temperature to ensure the normal progression of spermatogenesis. Rising temperatures affect spermatogenesis and eventually lead to a decline in male fertility or even infertility. However, the testes are composed of different cell types, including spermatogonial stem cells, spermatocytes, spermatozoa, Leydig cells, and Sertoli cells, which have differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Spermatozoa carries the task of accurate intergenerational transmission of paternal genomic genetic information, which is an important guarantee for species reproduction and species continuity. Testis are the main site of mammalian spermatogenesis and the only visceral organ located outside the body, which makes spermatogenesis extremely sensitive to the external environment [48]. Since spermatogenesis requires a relatively low-temperature environment, temperature is the most important environmental factor affecting spermatogenesis [49].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa carries the task of accurate intergenerational transmission of paternal genomic genetic information, which is an important guarantee for species reproduction and species continuity. Testis are the main site of mammalian spermatogenesis and the only visceral organ located outside the body, which makes spermatogenesis extremely sensitive to the external environment [48]. Since spermatogenesis requires a relatively low-temperature environment, temperature is the most important environmental factor affecting spermatogenesis [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of male reproductive cells, recent investigations have extensively explored the impact of heat stress on testis morphology, antioxidant status, and testicular biosynthesis [ 34 , 99 , 100 , 101 ]. Sertoli cells, known for providing structural and nutritional support for developing germ cells, have been a focus of scrutiny, with studies comprehensively examining the repercussions of heat stress on male reproductive cells, including Sertoli cells, spermatogonial stem cells, and Leydig cells [ 102 ]. Wang C et al [ 103 ] reported that HS induces oxidative stress and apoptosis in Sertoli cells, disrupting the normal spermatogenesis process.…”
Section: Impact Of Heat-stress-induced Oxidative Stress and Apoptosis...mentioning
confidence: 99%
“…Furthermore, another study noted that heat stress induced oxidative stress in Sertoli cells by suppressing the level of nuclear factor erythroid 2-related factor 2 (Nrf2) [ 107 ]. In addition, the effects of oxidative stress on Leydig cells have been briefly reviewed in recent studies [ 102 , 108 ]. Heat stress treatment inhibited cell viability, induced apoptosis, increased the activity of caspase 3 and the pro-apoptotic protein Bax, and decreased the expression of anti-apoptotic protein B-cell leukemia/lymphoma-2 (Bcl-2), concurrently activating endoplasmic reticulum (ER) stress markers such as glucose-regulated protein 78 (GRP78) and CCAAT/enhancer-binding protein homologous protein (CHOP) [ 109 ].…”
Section: Impact Of Heat-stress-induced Oxidative Stress and Apoptosis...mentioning
confidence: 99%
“…In this manner, the caspase cascade is eventually activated, resulting in protein degradation and cell death. In spermatocytes and sperm cells, the classical apoptotic pathway (mitochondrial apoptotic pathway) is primarily activated by heat stress (Cai et al, 2021). The pro-apoptotic BAX-BAK and anti-apoptotic BCL-2/BCL-XL proteins regulate apoptosis (Amaral et al, 2013).…”
Section: Ap Op Tos Ismentioning
confidence: 99%